2021
DOI: 10.1111/jocs.15418
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative outcomes between robotic mitral valve replacement and conventional mitral valve replacement

Abstract: Background Robotic mitral valve surgery continues to become widespread all over the world in direct proportion to the developing technology. In this study, we aimed to compare the postoperative results of robotic mitral valve replacement and conventional mitral valve replacement. Methods A total of consecutive 130 patients who underwent robotic mitral valve replacement and conventional mitral valve replacement with full sternotomy between 2014 and 2020 were included in our study. All patients were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
(23 reference statements)
2
13
0
Order By: Relevance
“…Advances in percutaneous techniques and the emerging competition since the 1990s have led surgeons to try to achieve these excellent results with less invasive methods. 4 Beyond the good cosmetic results, minimally invasive procedures are preferred because of the small size of the incision, less wound infection, less postoperative bleeding, and therefore less need for blood and blood products, and shorter intensive care and hospital stays. 5 Calafiore et al 6 However, it must be acknowledged that the difficulty of the surgical technique is known to be the main limitation for all previously described minimally invasive multivessel coronary grafting techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in percutaneous techniques and the emerging competition since the 1990s have led surgeons to try to achieve these excellent results with less invasive methods. 4 Beyond the good cosmetic results, minimally invasive procedures are preferred because of the small size of the incision, less wound infection, less postoperative bleeding, and therefore less need for blood and blood products, and shorter intensive care and hospital stays. 5 Calafiore et al 6 However, it must be acknowledged that the difficulty of the surgical technique is known to be the main limitation for all previously described minimally invasive multivessel coronary grafting techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Of the fourteen included studies, thirteen were retrospective comparative studies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) with the fourteenth paper not reporting exactly how the data accrual and analysis were performed (14) (Table 1). Eight studies either included or had separate data for matched patient cohorts, seven of which specifically indicated propensity score matching (PSM) (15,17,19,20,24,25,27), with the eighth study reporting that both cohorts were "matched" retrospectively with no statistical difference in any of the listed patient demographic data in the two cohorts (16).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Where reported, the operative technique for the RMVS was performed through a varying 2-to 5-centimeter anterolateral mini-thoracotomy and varying number of other access ports. Eleven studies reported the robotic surgical platform used (14)(15)(16)18,19,(21)(22)(23)(24)26,27), all of which used the da Vinci ® Surgical System (Intuitive Surgical Inc., Sunnyvale, California, USA). Ten of the fourteen included studies reported the robotic cross clamp method.…”
Section: Operative Detailsmentioning
confidence: 99%
See 2 more Smart Citations